Control de constitucionalidad y garantía de derechos fundamentales frente a la potestad presupuestaria del Estado en el Perú - Cobián Castro, Erika García (2025)
The general objective of this research is to contribute to constitutional reflection on the justification and scope of the actions of constitutional judges to control the budgetary powers of the State with the aim of guaranteeing fundamental rights. In this sense, it seeks to criticize whether budgetary reasons absolutely prevail over human rights., and aims to contribute to development a line of legalconstitutional argumentation aimed at strengthening the effectiveness of this control of constitutionality in Peru. The methodology used in the thesis is a dogmatic-legal one, insofar as its object of study and analysis focuses on the constitutional jurisprudence established by the Peruvian Constitutional Court on the relationship between fundamental rights and the budget Constitution. The critical analysis of the jurisprudence is framed within a post-positivist theory of law, constitutional budget law, international human rights law on rights and budgets, comparative German, Spanish and Colombian constitutional jurisprudence, and the applied research of specialised civil society and academic organisations. One of the main conclusions reached by the research is that the Peruvian Constitutional Court has developed as a tendentially active constitutional judge, compatible with a post-positivist conception of law and respectful of the legal framework defined by the Peruvian Constitution in terms of fundamental rights and the public budget. This tendency should be consolidated, extended and deepened through an intensification of the constitutionalisation of budget law, the development of budget analysis techniques, as well as its commitment to the values and principles of the constitutional state, the social dimension of this paradigm, fundamental rights and the justice of public spending.